Psychometric properties of an adapted Yemeni version of rejection sensitivity questionnaire / Sumaia Mohammed Radman Zaid - Sumaia , Mohammed Radman Zaid (2019)
Early rejecting experiences in significant relationships contribute to the development of rejection sensitivity (RS). Rejection sensitivity is the disposition to anxiously expect, perceive, and strongly react to rejection. The purpose of this study was to evaluate the psychometric properties of the Adapted Yemeni Version of Rejection Sensitivity Questionnaire (Y-RSQ) with adults through assessment of the measure’s reliability, validity, and utility. The measure that was used to help determine the validity of the Y-RSQ was the social anxiety (SA) questionnaire. The Y-RSQ and SA questionnaires were completed by a sample of 571 Yemeni students (males and females) at Sana’a University. Internal consistency reliability was calculated for the Y-RSQ and was satisfactory for research purposes the overall reliability being .82. 67% of the variance in observed total scores was due to the common factors, which indicated Y-RSQ has criterion-related validity. A Pearson Product Moment Correlation was performed between the Y-RSQ and SA scores. The analyses indicated a moderate, but significant positive relationship between Y-RSQ and SA (r = .50, p < .01). The findings of the confirmatory factor analysis indicated that the factor structure of the RSQ can be represented by a bifactor model: general rejection sensitivity factor and two group factors, rejection anxiety and expectancy of rejection. The findings suggested that the construct validity of the Y-RSQ is acceptable and that anxiety and expectation of rejection could bias people to readily perceive and strongly react to signs of rejection in different ways.